PENGARUH MANAJEMEN LABA DAN PERENCANAAN PAJAK TERHADAP NILAI PERUSAHAAN DENGAN MODERASI KEPEMILIKAN INSTITUSIONAL - Heni Sumiyati, 13.05.52.0171; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2017)
This research aims to test and analyze the effect of earnings management and tax planning on the value of companies with institutional ownership as a moderating variable on manufacturing companies listed on the stock exchange Indonesia.Â The population in this study is 462 manufacturing companies listed on the Indonesia Stock Exchange in 2013-2015. The sample selection was done by purposive sampling method. The analysis technique used multiple linear regression analysis. Moderate quasi model with interaction basis. The result of this analysis shows that the variable of earnings management doesnât have an effect on company value, tax planning doesnâthave an effect on firm value, institutional ownership have positive significant effect to firm value, tax planning with moderation of institutional ownership has positive significant effect to firm value, firm size has positive significant effect to value Company and profitability have a significant positive effect on company value.Keywords:Â Profit Management, Tax Planning, Institutional Ownership, Company Size, Profitability